A pilot study with adaptations to the Maudsley Method approach on workshops for carers of people with eating disorders. Issue 4 (12th December 2016) - Linacre, Stephen; Green, Jessica; Sharma, Vishal
Abstract : Purpose: Carers of people with eating disorders (EDs) experience high levels of burden which can lead to clinical levels of depression and anxiety, high levels of expressed emotion and can lead to a non-conducive environment to support recovery. The Maudsley Method skills-based workshops can empower carers to support people with ED to move towards recovery, reduce carer burden and high levels of distress. The paper aims to discuss these issues. Design/methodology/approach: Adaptations have been made to the Maudsley Method skills based workshops to include evidence based approaches from cognitive remediation therapy; mindfulness and acceptance commitment therapy. The adapted workshops were assessed via a pilot study with ten carers of people with ED using a mixed method design. The Experience of Caregiving Inventory and SF-36 were used to assess aspects of caregiving and carer wellbeing, respectively pre and post intervention. Thematic analysis was used to evaluate carers' views on the intervention. Findings: Results indicated that carers reduced their level of burden particularly in their experience of stigma, dependency and loss. Furthermore, positive aspects of the relationship with the person with the ED improved. Thematic analysis was used to obtain feedback from carers of the workshops. Qualitative data identified that carers improved their self-awareness, understanding of ED and the techniques they could use, and increased their social support. Research limitations/implications: Further research is required to compare the original workshops with this adapted intervention. Originality/value: Although this is a pilot study, the results suggest that further evidence based interventions could be added to the Maudsley Method approach to support carers.